Civil Rights Of Children Outside Married Due Isbat Nikah Of Polygamy (Analysis of Islamic Court of Rembang Decision No. 99 / Pdt.G / 2018 / PA.Rbg.) - Rofi'atun Rofi'atun; Akhmad Khisni; Rozihan Rozihan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study discusses the civil rights of children outside the mating due to confirmation of marriage polygamy, Problems taken author in this thesis is how the legal protection of children outside marriage related his civil rights especially on custody of marriage and inheritance rights to men as fathers biological, because the Indonesian Constitution the Act of 1945 and other regulations related to children's rights requires such a case, article 28 B (2) the result of amendments to the Act of 1945 states